Intraosseous administration into the skull: Potential blood-brain barrier bypassing route for brain drug delivery - Ji Hee Kang; Young Tag Ko (Wiley, 2023)
Abstract Progress in treating central nervous system (CNS) disorders is retarded owing to a limited understanding of brain disease pathology. Additionally, the blood-brain barrier (BBB) limits molecular entry into the brain. Many approaches for brain drug delivery to overcome the BBB, such as BBB permeability enhancement, transient BBB disruption, and direct surgical administration have been explored with limited success. Recent research has shown that direct vascular channels exist between the skull bone marrow and the meninges, allowing myeloid and lymphoid cells to migrate. We hypothesized that these direct channels may also allow brain drug delivery from the skull bone marrow to the brain. In this study, for the first time we propose intraosseous administration of drugs into the skull (intracalvariosseous [ICO]) as a novel approach for brain drug delivery via BBB bypassing routes. We tested the feasibility of the approach by applying nine representative compounds over thinned mouse skulls to simulate ICO and measuring the compound entry level in the brain compared to that after systemic administration. Surprisingly, we found that the skull is not completely impermeable to drug penetration into the brain and the tested compounds reached the brain tissue several tens‐to‐hundred times higher by ICO than systemic application. These findings suggest a role for the BBB bypassing route from skull to brain, apart from the systemic route, in the drug entry into the brain after ICO. This approach should be applicable to other CNS drugs and even BBB impermeable drugs. Overall ICO provides an innovative and advantageous pathway for effective treatment of brain diseases.